Influence of breeding and length of feeding period on carcass characteristics and palatability of beef - Tuma, H.J.; Kropf, Donald H.; Mackintosh, D.L.; Alschwede, G.A. (Kansas Agricultural Experiment Station, 2011)
Carcass measurement, muscle quality, and palatability data have been collected on 88 paternal half-sib Angus steers. At weaning they were subdivided into one of the 11 nutritional and management regimes shown in Table 58. Phase I involved feeding from 0 to 224 days after weaning. Phase II was essentially deferred feeding. The intermittent slaughter of animals from both phases made possible the study of muscle and fat tissue development within as well as between phases. Quantity and quality of muscle are the two factors that determine true beef carcass value.
Keywords: Beef; Carcass characteristics; Palatability; Muscle tissue